A translational model for early childhood intervention: developing, implementing, and scaling-up effective practices - Kallen R. Shaw; Ramzi G. Salloum; Patricia A. Snyder (Frontiers Media S.A., 2023)
Early intervention (EI) researchers (i.e., those focused on children birth to age 3 and their families who experience early vulnerabilities) often engage in translational research and implementation science at the intersection of public health, pediatrics, and EI. There is currently a significant research-to-practice gap in EI despite ongoing efforts to close it. Translational research and implementation science are promising approaches to promote transdisciplinary collaborations among researchers and to move EI research into practice, thus supporting positive outcomes for young children and families. This commentary proposes a contemporary alignment of translational research phases for EI. Two literature reviews served to inform development of this alignment: (1) a narrative literature review identified existing applications of translational phases to EI; and (2) a rapid review identified examples of existing behavior-focused translational models across disciplines. Several case examples of current translational research being conducted in EI are discussed and classified according to their respective translational phase. The proposed alignment and case examples provide a basis for transdisciplinary conversations among those working across the various fields and disciplines relevant to EI research. A shift in EI research to reflect a translational and implementation focus will help bridge the research-to-practice gap and, most importantly, speed the movement of scientific evidence into real-world contexts to positively impact young children and families.